Strategi Mengatasi Data Breaches di Era Industri 4.0: Kasus Data Breaches Bank Rakyat Indonesia - Annisa Ayu Handayani; Balqis Naura Izzati; Diana Nur'azzah; Khoirunnisa Khoirunnisa; Ida Farida Adi Prawira (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
To analyze the strategies implemented by Bank Rakyat Indonesia (BRI) in addressing data breaches in the Industry 4.0 era by identifying contributing factors such as user awareness, security system weaknesses, and the effectiveness of mitigation policies. This study uses a qualitative approach with descriptive methods through document analysis with purposive sampling techniques of official BRI reports and relevant scholarly literature. The research findings indicate that the main causes of data breaches are low digital security awareness, weaknesses in authentication systems, and the rise of phishing attacks. BRI has responded by implementing several key strategies, including digital literacy education, the use of layered security technologies such as multi-factor authentication and AI-based transaction monitoring, as well as early detection and incident response systems. These measures have successfully prevented hundreds of thousands of unauthorized access attempts throughout 2023. The implications of this study emphasize that increasing public awareness of digital security and continuously improving technological infrastructure are crucial steps in minimizing data breach risks and enhancing public trust in digital banking services.